2024
DOI: 10.1111/head.14656
|View full text |Cite
|
Sign up to set email alerts
|

CCH attack frequency reduction after psilocybin correlates with hypothalamic functional connectivity

Martin K. Madsen,
Anja Sofie Petersen,
Dea S. Stenbæk
et al.

Abstract: ObjectiveTo evaluate the feasibility and prophylactic effect of psilocybin as well as its effects on hypothalamic functional connectivity (FC) in patients with chronic cluster headache (CCH).BackgroundCCH is an excruciating and difficult‐to‐treat disorder with incompletely understood pathophysiology, although hypothalamic dysfunction has been implicated. Psilocybin may have beneficial prophylactic effects, but clinical evidence is limited.MethodsIn this small open‐label clinical trial, 10 patients with CCH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Research indicates that psilocybin administration can lead to effects such as silliness, laughter, and playfulness, which may be perceived as unconventional but can be modulated to align with the desired clinical outcomes [94]. It is important to note that psilocybin has potent psychedelic properties and is illegal in most countries, with reports of serious negative health-related outcomes in non-clinical settings due to poorly regulated behavior [95][96][97]. Studies have found that younger individuals are more likely to require emergency medical treatment after using psilocybin than older individuals.…”
Section: Psilocybin For End-of-life Care and Cancer-related Depressionmentioning
confidence: 99%
“…Research indicates that psilocybin administration can lead to effects such as silliness, laughter, and playfulness, which may be perceived as unconventional but can be modulated to align with the desired clinical outcomes [94]. It is important to note that psilocybin has potent psychedelic properties and is illegal in most countries, with reports of serious negative health-related outcomes in non-clinical settings due to poorly regulated behavior [95][96][97]. Studies have found that younger individuals are more likely to require emergency medical treatment after using psilocybin than older individuals.…”
Section: Psilocybin For End-of-life Care and Cancer-related Depressionmentioning
confidence: 99%
“…A Danish study reports a 30% reduced attack frequency in patients suffering from chronic CH. Also, a negative correlation of changes in hypothalamic-diencephalic functional connectivity with relative reduction in attack frequency was found [20]. The second study by Schindler et al recruited both episodic (ECH) and chronic (CCH) CH patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by the Swedish Health Agency from 2020, cannabis use is generally lower in Sweden than many other European countries. Cannabis use is most prevalent in the age group [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] with an estimated 8% of men and 5% of women that age using it (https://www.folkhalsomyndigheten.se/livsvillkor-levnadsvanor/andts/andts-anvandningoch-ohalsa/anvandning/narkotikaanvandningen-och-utvecklingen/cannabis-och-folkhalsa/ (accessed on 12 March 2024)). Though the Swedish Health Agency reports a more positive attitude toward cannabis use as compared to other narcotics in the general Swedish population, the majority still believe it should not be legal.…”
Section: Introductionmentioning
confidence: 99%